Pre-procedural expression of Mac-1 and LFA-1 on leukocytes for prediction of late restenosis and their possible correlation with advanced coronary artery disease. - Rahimi, K; Maerz, H; Zotz, R; Tárnok, A (2003)
BACKGROUND: The activation status of the inflammatory system has been suggested to play an important role in predicting restenosis. Activation of leukocyte adhesion molecules occur after coronary intervention and the level of activation correlates to restenosis. However, little is known about the specific role of adhesion molecules before intervention. The purpose of this study concerned the search for differences in the expression level of selected adhesion molecules to identify suitable tools for the pre-procedural identification of restenosis patients prior to angioplasty. METHODS: Blood samples of 31 patients undergoing elective coronary angiography were obtained just before intervention. Seven healthy volunteers were also enrolled. Surface expression of leukocyte adhesion molecules Mac-1 (CD11b/CD18), LFA-1 (CD11a/CD18), L-Selectin (CD62L), ICAM-1 (CD54), and MHC-II (HLA-DR) were assessed by flow cytometry. Patients with a successful angioplasty received a follow-up angiography after six months. RESULTS: According to the clinical and angiographic data, patients were divided into four groups: control (N = 14), no restenosis (N = 11), restenosis (N = 4), and advanced coronary artery disease (CAD, N = 9). The restenosis group and the advanced CAD group showed higher expression of Mac-1 and LFA-1 on monocytes and neutrophils compared to the other groups. Using the pre-procedural expression levels, patients with restenosis could be predicted by discriminant analysis with CD11a, CD11b, and CD18 (average recognition index = 95.5%). CONCLUSIONS: The data of this pilot study indicate that pre-procedural activation status of CD11a and CD11b may play a role in the subsequent development of restenosis. Moreover, CD11a, CD11b, and CD18 may be helpful as indicators for the progression of CAD. Copyright 2003 Wiley-Liss, Inc.